SKRINING PENYAKIT TIDAK MENULAR (PTM) DALAM UPAYA PENINGKATAN KESEHATAN MASYARAKAT RT 03 LEMPUING - Wijaya, Andra Saferi; Nafratilova, Mercy; Marita, Zadam; Amante, Fiona; Saputri, Apreni (Poltekkes Kemenkes Bengkulu, 2024)
Non-communicable diseases (NCDs) are one of the health problems that cause many deaths in the world. This non-communicable disease is not transmitted from one individual to another. The public must know how to detect this non-communicable disease early, so efforts are needed to increase public knowledge. The aim of community service through Non-Communicable Disease Screening by Bengkulu Ministry of Health Polytechnic Students in RT 3, Lempuing Village, Ratu Agung District is to provide knowledge, especially to the Elderly Community, about non-communicable diseases and the importance of carrying out regular blood pressure checks and sugar checks. blood and cholesterol to detect non-communicable diseases. Community service activities are carried out for screening and education about PTM to the community in the area. The health examination included measuring blood pressure, instantaneous blood sugar (GDS), cholesterol, height, weight and abdominal circumference for the 45 elderly people who attended. This activity was carried out at a posbindu event using a 5 table system. The results of this service were found from 43 respondents, including 31 people with hypertension, 2 people with diabetes mellitus, 11 people with prediabetes, 11 people with high cholesterol and 12 people with moderate cholesterol.